Osseo Densification - A Comprehensive Review on Novel Approach - Vijay Ebenezer1 , Balakrishnan Ramalingam2 , M.Elumalai3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Success of a dental implant depends on osseointegration which is the direct structural and functionalconnection between the dental implant and the alveolar bone. Successful osseointegration requires bothprimary stability (mechanical stability) between the implant and the bone and secondary stability (biologicalstability) which occurs during bone remodelling during healing.